The checklist of liverworts (Hepaticae) and hornwarts (Anthocerotae) of Vietnam update based on literature survey - Bakalin, Vadim; Sinh, Nguyen Van (Academia Journal of Biology, 2017)
The checklist of liverworts and hornworts of Vietnam was published more than 50 years ago. The aim of this study is to provide new checklist based on literature survey. The updated checklist includes 5 species of hornworts and 296 species of liverworts. The largest taxonomic group in regional hepatic flora is Lejeuneaceae that counts 178 species. It is estimated that the known taxonomic diversity will exceed 400 taxa once purposeful researches would be made. Received 10 October 2016, accepted 20 December 2016